Khoa học công nghệ phục vụ phát triển bền vững Tây Nguyên - Kỳ, Nguyễn Đình (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Science and technology for sustainable development in Tay Nguyen Tay Nguyen areas compsises series of plateaus, having an important geo-political significances with sensitive, rich ecosystem and special culture. The region has huge potentiality in position, natural and human resources, and it has great importance in the country. Because of exploiting resources unreasonably, Tay Nguyen is facing a lot of challenges of environmental conflicts and development. Therefore, it is necessary to re-evaluate sively its states of economy, society and nature and proposing science and technology program for sustainable development. With interdisciplinary research approaches, multidisciplinary, economy - eco environment, to make Tay Nguyen became a dynamic economic region of the country with a model of international special zone of economy “Vietnam - Laos - Cambodia”. The ideas are presented in the scientific and technological program “Generally research and evaluate resources - environment, economy - society and propose scientific and technological basis for strategies of sustainable development in Tay Nguyen in period 2011-2020 and Vision 2030” (called The program III of Tay Nguyen).